Creating a culture of empowerment and accountability at St. Martin de Porres High School (A) - Howard, Liz Livingston, (SAGE knowledge. Cases., 2016)
Change is hard for all but perhaps more difficult for school leaders and other nonprofit organizations. The role that culture plays in a mission-driven organization can often be an impediment to change. This case uses a unique education institution, St Martin de Porres School of the Cristo Rey Network, to illustrate the importance of culture in implementing change.